Sekolah Lapang Sistem Bertanam Padi baris Legowo 2:1 Sebagai Upaya Untuk Meningkatkan Produksi Tanaman Padi (Oriza Sativa) - Nataliningsih, Nataliningsih; Gantini, Tuti; Sondari, Nunung; Dasipah, Euis; Suseno, Gijanto Purbo; Mulyana, Tatang; Aas, Ani (Politeknik Negeri Lampung., 2024)
The rice production improvement program is carried out to meet the needs and food security of a country, the results of cultivation and post-harvest innovations are delivered in agricultural counseling to be implemented by farmers in an effort to increase their agricultural yields . One of the results of innovation is how to grow rice with the legowo row 2:1 planting system can be socialized to farmer groups through Field Schools so that farmers can more easily understand and participate in practical demonstrations in the field as part of their experience. The research uses aquantitative approach, and a type of explanatory research type survey research that highlights the causal relationship between research variables and tests the hypotheses formulated. The subject of the study was the Sindang Kerta farmer group, West Java, with a total rice field area planted with rice as much as 2,396 ha by 90 farmers. This study used 2 types of variables, namely free variables and bound variables, each of the variables studied was a free variable 1 (X1) is the institutional or dynamic of farmer groups, the free variable 2 (X2) is a row legowo 2:1rice planting system, and the bound variable is an increase in rice production produced (Y). The data obtained were analyzed using SEM PLS. The results of the description of the farmer group institution show that the average value is >4.01, which means that the farmer group institution is very good, Based on the values of path coefficients or path coefficients, the resulting structural equation is as follows: Y = 0.631 X1 – 0.152 X2 which means that group institutions have a positive effect while the legowo row 2:1 planting system has less influence on the production of rice produced. Key word: Planting system, farmer group, yields